The Music Teacher I’d Like: Lessons Learnt From Students - Economidou Stavrou, Natassa (Frontiers in Education, 2022)
The present study investigates what makes and what doesn’t make an ideal music teacher according to secondary school students’ views and perceptions. Is it a matter of personality characteristics, subject knowledge and skills or a matter of pedagogy? Or is it a combination of the aforementioned? And more specifically, what are those qualities, personal characteristics and competencies of the ideal music teacher through the eyes of students? 518 secondary school students participated in the study by completing an anonymous questionnaire. The findings reveal that the characteristics of the ideal music teacher deemed more important for secondary school students fall mainly in the category of personality and interpersonal characteristics, with pedagogical and subject knowledge and skills following, with much smaller percentages. The students’ voices call firstly for a polite, friendly, with sense of humor, kind teacher, patient, pleasant, fair and creative. By building on the findings, the paper establishes recommendations for music teacher education and teacher effectiveness, as these are framed through the students’ eyes and experiences.